Addisonian Pigmentation - The Great Mimicker - A Review - Damini Verma; Rashmi Sarkar; Vibhu Mendiratta; Amol Srivastava (Wolters Kluwer Medknow Publications, 2024)
Skin colour usually depends upon melanin, haemoglobin, and carotenoids. Pigmentary disorders indicate an increased amount of melanin, leading to a darker colour of the skin, called hypermelanosis. Addison's disease is a rare endocrinal disorder with severe oral and systemic manifestations. Any form of diffuse skin hyper-pigmentation which is more pronounced on sun-exposed areas mimics Addison's disease and is called Addisonian pigmentation. Pigmentation often precedes other manifestations by months to years and hence can lead to early diagnosis and can prevent life-threatening adrenal crisis. The most common cause of adrenal insufficiency in developing countries is tuberculosis. A similar pattern of pigmentation has been reported in Cushing's syndrome, ectopic ACTH-producing tumours, vitamin B12 deficiency, and thyrotoxicosis. Addisonian pigmentation can be a manifestation of multiple systemic diseases; hence, an inter-disciplinary approach is needed with extensive clinical and laboratory evaluation. It is not merely a cosmetic concern. Not much data are available in the literature regarding this entity. This brief review serves as an important source for clinicians to stay up-to-date regarding the history, clinical presentation, differential diagnosis, and management of this entity.